Maize Maize Development with Planting Methode the Zig-Zag System for Increasing Productivity in the Tidal Swampland: Pengembangan Jagung dengan Metoda Tanam Sistem Zig-Zag untuk Meningkatkan Produktivitas di Lahan Rawa Pasang Surut - Khairatun Napisah; Simatupang, Raylander Smith; Maftu'ah, Eni (Universitas Bangka Belitung, 2025)
Maize is the second main food commodity in the Indonesian economic system. The self-sufficiency was achieved in 2017, however the nation's corn production to decrease and import value in 2018 and 2019 increased by 60.98% and 25.49% or about 1.15 million tons and 293,210 tons. The projection of cornproduction until 2024 will increase by about 24.04 - 24.98 million tonsof dry peel with a growth rate of about 2.05%. The development of maize in the tidal swampland by the extensification of the planting area is very possible, particularly on the C, C/D, and D overflow type land that is about 3.36 million hectares wide. According to the growth rate, the planting area increasedby about 75,000 ha would contribute about 396.750 tons/year to the nation's production. One of the planting methods that could be applied for maize plants to increase productivity and corn production is the Zig-Zag System. The zig-zag system could increase plant population by around 60-80% and yield 30-40% per hectare. The development of hybrid variety with the Zig-Zag system by the 75 x 25 x 12.5 cm spacing 100-hectare wides in the acid sulfate land conducted in South Kalimantan, could be increasing the corn productivity achieved 14 ton/ha dry peel with 15% water content. The development of maize with planting methods the zig-zag systems in the tidal swampland very prospectively to supporting an increase of nation corn production.